Midwives’ knowledge, attitudes and learning needs regarding antenatal vaccination - Regan, Annette; Hauck, Yvonne; Nicolaou, L.; Engelbrecht, D.; Butt, J.; Mak, D.; Priest, R.; Cukierman, R.; Effler, P. (Churchill Livingstone, 2018)
Objective: To determine the knowledge, attitudes and learning needs of midwives regarding antenatal vaccination. Design and setting: A cross-sectional, paper-based survey of midwives employed at the only public tertiary maternity hospital in the Australian state of Western Australia between November 2015 and July 2016. Participants: 252 midwives providing care in antepartum, intrapartum, and/or postpartum settings. Measurements: Self-reported responses to a 41-item survey. Findings: The vast majority of midwives supported influenza and pertussis vaccination for pregnant women, with 90.0% and 71.7% reporting they would recommend pertussis and influenza vaccine, respectively, to a pregnant friend or family member, and almost all stating that midwives should administer vaccines to pregnant patients (94.8%). Seven out of ten midwives (68.1%) responded correctly to all knowledge items regarding vaccines recommended during pregnancy; 52.8% demonstrated correct knowledge regarding vaccine administration despite only 36.6% having attended an education session on antenatal vaccination in the previous two years. Nearly all midwives (97.3%) expressed a need for more education on vaccine administration. The most commonly reported barrier to administering influenza (61.3%) and pertussis (59.0%) vaccination was having staff available with the certification required to administer vaccines. Key conclusions: Midwives view antenatal vaccination as their responsibility and are interested and receptive to education. Implications for practice: There is an unmet need and demand among midwives for professional development that would enable them to recommend and administer vaccines to pregnant women in accordance with national immunisation guidelines and integrate vaccination into routine antenatal care.